Վահան Թեքեյանի գործունեությունը Լիբանանում և Սիրիայում 1923 թվականին - Ժամխարյան, Կարո
This article is dedicated to the activity one of Armenian national character and great writer Vahan Tekeyan in Syria and Lebanon during 1923 year. Throughout 1923s Vahan Tekeyan, being a member of Liberal Party <<Ramkavar>>, was taking serious steps for confirming solidarity between various parties and organizations of Diaspora as well as he desired to declare Soviet Armenia as a center of whole Armenian nation. He also emphasized the importance of the creation of the the joint Diaspora Organization. Tekeyan's all these intentions became obvious in 1923 during his visit to Syria and Lebanon. However, the parctic steps were taken later, particulary in 1927. This part of Tekeyan's activity is too important both for the history of Diaspora and for the analyze of Tekeyan's biography. В этой статье освещается деятельность народного деятеля, великого писателя Ваана Текеяна в Ливане и Сирии в 1923 г..В 1920 г. Ваан Текеян ,являясь членом партии "Рамкавар азатакан", предпринимал решительные шаги для утверждения солидарности между действующими в Спюрке различными армянскими политическими партиями и организациями, и с целью сделать Советскую Армению центром всех армян. На пути осуществления этой задачи считал также важным делом создание общедиаспорской организации. Эти намерения Текеяна становятся явными во время его визита в Ливан и Сирию в 1923г.. Но деловые шаги в этом направлении делаются позднее, в 1927 г.. Этот эпизод деятельности Текеяна был очень важным как для истории диаспоры, так и с точки зрения анализа биографии народного деятеля.
Keywords: Հայոց պատմություն; Վահան Թէքէեան; Բարեգործական միություն